The ionospheric F2 region winter anomaly and its dependence on solar activity in the northern and southern hemisphere. - Eduardo Francisco Garat; Ana Martínez Pulido (Geofísica Internacional, 1997)
Data from two ionospheric sounders each from the northern and southern hemisphere, are used for a statistical analysis of foF2 monthly medians for summer and winter and high and low solar activity. The winter anomaly is always present in the northern hemisphere and only occasionally in the southern one. Statistical results suggest that the F2 region behaviour is different from one hemisphere to the other. In the northern hemisphere explanatory variability is 82 to 85% at night and 60 to 83% at noon. At night, in the southern hemisphere, the explained variability oscillates between 63 and 77%. However, at noon, it becomes necessary to look for other explicative variables since only 28 to 45% of the variability of ΔfoF2(12) is explained. These results may be due to the South Atlantic geomagnetic anomaly, lowering the geomagnetic mirror points and enhancing trapped particle precipitation in the denser atmosphere. Thus, heating should be larger in the South Atlantic region, inhibiting convection from the northern summer to the southern winter.